Penerapan Irigasi Tetes Bawah Permukaan Bertekanan pada Budidaya Tomat - Muhammad Idrus (Jurnal Ilmiah Teknik Pertanian - TekTan, 2013)
The research was conducted at the Research Field of Lampung State Polytechnic, Bandar Lampung from July to September 2013.  The objectives of the research was To test the pressure subsurface drip irrigation performances in tomato cultivation.  The result of the research showed that tomato production and  irrigation water productivity by the pressure subsurface drip irrigation method was higher compared to furrow irrigation method.  Tomato production and irrigation water productivity by the pressure subsurface drip irrigation method were 1,319 kg/plant and 23,974 kg/m3 respectively, but by the furrow method were 1,165 kg/plant and 2,774 kg/m3.  Amount of iririgation water application on tomato cultivation by the pressure subsurface drip irrigation method for one periode of planting was only 55 liters but by the furrow method was 420 liters.  There for the amount of irrigation can be conserved on tomato cultivation by the the pressure subsurface drip irrigation method was 86,90%  compared to the furrow method. Keywords: pressure subsurface drip  irrigationand furrow method, tomato, production, irrigation water application and irrigation water productivity.